The Effect of Macroeconomic Indicators, Crude Oil Prices, and the Dow Jones Index on the Jakarta Composite Index - Santosa, Perdana Wahyu; Roselli, Salsabila (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2023)
This research aims to analyze the influence of macroeconomic factors, such as  Exchange Rate, BI Rate, Inflation, Gross Domestic Product, Crude Oil Price, and Dow Jones Industrial Average Index (DJIA) on the Jakarta Composite Index (JCI) for the 2014-2018 period. The analytical method used is the Error Correction Model (ECM) with a significant level of 5% with E-views 10 software. The results of partial research show that in the short and long term, the Exchange Rate and Oil Price significantly negatively affect the JCI and BI Rate in the short term and have a significant negative relationship with the JCI, inflation, and Gross Domestic Product a negative and insignificant relationship with the JCI and the Dow Jones Index in the short and long term has a significant positive relationship with the JCI. The simultaneous research results show that the Exchange Rate, BI Rate, Inflation, Gross Domestic Product, Oil Price, and the DJIA simultaneously significantly influence the dependent variable, namely JCI. According to the Islamic review, activities related to Exchange Rate, BI Rate, Inflation, GDP, Crude Oil Prices, the Dow Jones Index, and the JCI are allowed. However, they must comply with Islamic law and regulations.